Tuning the Triplet Excited State of Bis(dipyrrin) Zinc(II) Complexes: Symmetry Breaking Charge Transfer Architecture with Exceptionally Long Lived Triplet State for Upconversion. Issue 65 (14th October 2020) - Mahmood, Zafar; Rehmat, Noreen; Ji, Shaomin; Zhao, Jianzhang; Sun, Shanshan; Di Donato, Mariangela; Li, Mingde; Teddei, Maria; Huo, Yanping
Abstract: Zinc(II) bis(dipyrrin) complexes, which feature intense visible absorption and efficient symmetry breaking charge transfer (SBCT) are outstanding candidates for photovoltaics but their short lived triplet states limit applications in several areas. Herein we demonstrate that triplet excited state dynamics of bis(dipyrrin) complexes can be efficiently tuned by attaching electron donating aryl moieties at the 5, 5′‐position of the complexes. For the first time, a long lived triplet excited state ( τ T =296 μs) along with efficient ISC ability ( Φ Δ =71 %) was observed for zinc(II) bis(dipyrrin) complexes, formed via SBCT. The results revealed that molecular geometry and energy gap between the charge transfer (CT) state and triplet energy levels strongly control the triplet excited state properties of the complexes. An efficient triplet–triplet annihilation upconversion system was devised for the first time using a SBCT architecture as triplet photosensitizer, reaching a high upconversion quantum yield of 6.2 %. Our findings provide a blueprint for the development of triplet photosensitizers based on earth abundant metal complexes with long lived triplet state for revolutionary photochemical applications. Abstract : Exploiting a structural control strategy we tuned the triplet excited state dynamics of zinc(II) bis(dipyrrin) complexes. Efficient intersystem crossing and long lived triplet state (296 μs) were accessed in the complexes, attaining a better matching of charge transfer and triplet energies with minimal non‐radiative energy losses. This is the first attempt to utilize an earth abundant organometallic framework with efficient symmetry breaking charge transfer as a triplet photosensitizer in triplet–triplet‐annihilation (TTA) upconversion.